Analisis Implementasi Wakaf Tanah di Kecamatan Pandak Kabupaten Bantul - Sukarno Sukarno; Supriyono Supriyono; Miftachul Alfin; Fattah Setiawan; Moh. Shofiyul Huda MF; Busyro Busyro (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
This Qualitative research is to see the suitability of land waqf implementation, especially in the administrative area of ​​the Office of Religious Affairs (KUA), Pandak District, Bantul Regency, with the prevailing regulations in Indonesia. The sociological juridical approach was chosen in analyzing the data collected by observation, documentation and in-depth interviews. Some of the informants are the Registration Officer for the Akta Ikrar Waqf (PPAIW KUA and staff); Nadzir Legal Entity; and individual Wakif in Pandak District. The implementation of land waqf in Pandak District is in accordance with the applicable provisions, namely Law Number 41 of 2004 concerning Waqf. However, several obstacles, especially in land law certainty and the active participation of all parties involved in land ownership, must receive immediate attention. Socialization regarding Law N0. 41 of 2004 concerning Waqf can be implemented in a sustainable manner so that the benefits can be extended to the productive waqf area. The action can be through face-to-face counseling or community recitation activities in addition to the use of electronic and print media.